2015
DOI: 10.3923/ijbc.2015.79.85
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Preservation of Commercial Important Fungi in Glycerol at 4°C

Abstract: Preservation of commercial and research important fungi for long time period is a very tedious job. Mostly cryopreservation technique in liquid nitrogen is used for long term preservation. In this work 15 different species of commercial and research important fungi are preserved at 4°C in different concentration of glycerol using two different methods (Slant culture and Slice cut method). In slant culture method at 50% of glycerol, 100 and 86.66% of fungi are viable upto 24 and 30 months of preservation, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Therefore, the isolation procedures, conservation and use of microorganisms, although established in laboratory routine, are important for the research development and obtaining products of economic interest [11]. In such a way, the method of maintenance of microorganisms requires that these should be conserved under low biological activity, focusing on the preservation of sporulation and pathogenicity characteristics [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the isolation procedures, conservation and use of microorganisms, although established in laboratory routine, are important for the research development and obtaining products of economic interest [11]. In such a way, the method of maintenance of microorganisms requires that these should be conserved under low biological activity, focusing on the preservation of sporulation and pathogenicity characteristics [12].…”
Section: Introductionmentioning
confidence: 99%
“…Water may be played a role for reducing fungal metabolism to very low levels by preventing desiccation and diminishes gas exchange. Furthermore, the current study revealed that preservation in glycerol 30% at RT (G30%.RT) could be considered as alternative method for H. maydis preservation since it exhibited a good degree of stability of the tested characteristics (Paul et al, 2015). However, Shearer et al (1974) reported that 24 strains of Septoria stored in soil up to 1 year were recovered by 100% with stability of their pathogenicity.…”
Section: Discussionmentioning
confidence: 77%
“…After that, 1.8 mL of the suspension with parts of colonized agar of each concentration were added individually in each unit (15 vials for each treatment). Then vials of each concentration of each isolate were stored at RT, 4°C and -20°C for 3, 12 and 24 months (Paul et al, 2015).…”
Section: Preservation In 10 and 30% Glycerolmentioning
confidence: 99%
“…The isolate was maintained on Sabouraud's dextrose agar (Oxoid, Basingstoke, Hamshire, UK) slopes and stored at 4 °C. Glycerol (50%) stocks were prepared for long‐term preservation at −80 °C 16 . The reference strain for antimicrobial activity assessment, S. aureus ATCC 25923, was obtained from the American Type Culture Collection (ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical isolate of C. albicans CI-24 was obtained from El-Demerdash Hospital, Cairo, Egypt. The isolate was identified by sequencing of the 28S rRNA genes and the sequence assembly was conducted using Bioedit 16 The reference strain for antimicrobial activity assessment, S. aureus ATCC 25923, was obtained from the American Type Culture Collection (ATCC).…”
Section: Microorganismsmentioning
confidence: 99%